Jawabanmu

2014-03-31T06:10:09+07:00
F(g(x))=3x^2-x-3/x+2
f(x)=3x-1
3(g(x))-1=3x^2-x-3/x+2
gmn nih, ada per.nya
(3g(x)-1)(x+2)=3x^2-x-3
3xg(x)+6g(x)-x-2=3x^2-x-3
3xg(x)+6g(x)=3x^2-x-3+x+2
3g(x)(x+2)=3x^2-1
3xg(x)(x+2)=(3x-1)???????
ah, mav, saya blom ahli.
2014-03-31T07:49:24+07:00
f(x) = 3x - 1 
(f o g)(x) =  \frac{3 x^{2} - x - 3}{x+2}
maka g(x) =
?
(f o g)(x) =  \frac{3 x^{2} - x - 3}{x+2}
f (g(x)) =
 \frac{3 x^{2} - x - 3}{x+2}
3 (g(x) - 1 =  \frac{3 x^{2} - x - 3}{x+2}
3 (g(x)) = \frac{3 x^{2} - x - 3}{x+2} + 1
3 (g(x)) = \frac{3 x^{2} - x - 3}{x+2} +  \frac{x+2}{x+2}
3 (g(x)) = \frac{3 x^{2} - 1}{x+2}
   g(x)  = \frac{3 x^{2} - 1}{x+2} .  \frac{1}{3}
   g(x)  = \frac{3 x^{2} - 1}{3x+6}

semoga membantu :) jadikan yang terbaik ya :))